Indoxyl Sulfate Promotes Arterial Thrombosis in Rat Model via Increased Levels of Complex TF/VII, PAI-1, Platelet Activation as Well as Decreased Contents of SIRT1 and SIRT3 - Karbowska, Malgorzata; Kaminski, Tomasz W.; Znorko, Beata; Domaniewski, Tomasz; Misztal, Tomasz; Rusak, Tomasz; Pryczynicz, Anna; Guzinska-Ustymowicz, Katarzyna; Pawlak, Krystyna; Pawlak, Dariusz (Frontiers in Physiology, 2018)
Patients suffering from chronic kidney disease (CKD) are at 20-fold higher risk from the deaths of cardiovascular diseases (CVD), primarily thrombosis following vascular injury. CKD is connected with retention of uremic toxins, especially indoxyl sulfate (IS), that are currently considered as a non-classical CKD-specific risk factor for CVD. The present study aimed at examining the effect of chronic exposure to IS on hemostatic system and arterial thrombosis in model without greater interferences of uremic milieu consisting of additional uremic toxins. 48 male Wistar Crl:WI (cmdb) rats were divided into three groups: one control group and two experimental groups, which were exposed to 100 mg/kg of body weight (b.w.)/day or 200 mg/kg of b.w./day of IS in drinking water during 28 days. Control group received water without IS. At the end of experiment, the induction of arterial thrombosis was performed. We investigated the IS impact on thrombosis incidence, clot formation kinetics and strength, platelet activity, aortic contents of sirtuin (SIRT) 1 and SIRT3, hemostatic system, cardiorespiratory parameters, plasma and urine biochemistry, as well as thrombus, kidney and liver histology. Obtained data revealed that chronic exposure to IS promotes arterial thrombosis via increased level of complex tissue factor/factor VII, plasminogen activator inhibitor-1 (PAI-1), platelet activation as well as decreased aortic levels of SIRT1 and SIRT3. Therefore, we hypothesize that IS enhances primary hemostasis leading to augmented formation of platelet plug with increased amount of fibrin as well as affects secondary hemostasis through influence on plasma coagulation and fibrinolysis factors that results in increased clot formation kinetics and strength. Described findings may contribute to a better understanding of mechanisms leading to increased thrombotic events in CKD patients with elevated IS level.